Low-cost experimental application of real-time kinematic positioning for increasing the benefits in cereal crops - Tayebi, Abdelhamid; Gómez, Josefa; Fernández, Marián; de Adana, Francisco Sáez; Gutiérrez, Oscar (International Journal of Agricultural and Biological Engineering, 2021)
Traditional agriculture is facing several challenges worldwide such as increased population growth, rapid forestry and urbanization, resource scarcity, climate change, environmental pollution, competition among different markets. Hence, farmers need to improve productivity in order to maintain the output level. This study attempted to evaluate the benefits of using Real-Time Kinematic (RTK) positioning in precision agriculture through a series of real measurements carried out when farming cereals. All farming management actions involved in the cereal crop process (raise fallow, plow, sow, fertilize, mow, and harvest) have been done using an automatic guidance system that has reduced costs. A reduction of 20% has been quantified in the fuel, the amount of fertilizer, the labor costs and the hours of work. Consequently, the environmental impact has been also reduced. An inexpensive system consisting of a reference base station near the field and a mobile unit mounted on the test vehicle has been installed in order to increase the benefits in cereal crops. Global Navigation Satellite System (GNSS) systems including Global Positioning System (GPS), GLONASS, Galileo and Beidou have been used in the analysis. This research serves as a practical guide to implementing a low-cost guidance system to achieve best management practice.Keywords: real-time kinematic, low-cost, positioning, benefits, guidance system, cerealDOI: 10.25165/j.ijabe.20211403.5812Citation: Tayebi A, Gomez J, Fernández M, de Adana F S, Gutiérrez O. Low-cost experimental application of real-time kinematic positioning for increasing the benefits in cereal crops. Int J Agric & Biol Eng, 2021; 14(3): 194–199.